The Application of Giemsa Staining in Identifying Helicobacter pylori in Oral Biopsies: A Comparative Study with Immunohistochemistry - Vijay S. Rajak; Amit K. Srivastava; Sachin S. Yadav; Abhishek Mehta (Journal of Pharmacy and Bioallied Sciences)
Background: Helicobacter pylori (H. pylori), a significant pathogen in gastrointestinal diseases, has been implicated in various oral pathologies. Accurate detection of H. pylori in oral biopsies is crucial for understanding its role in oral diseases. Materials and Methods: A total of 100 oral biopsy samples were collected from patients presenting with suspected oral lesions. The samples were subjected to Giemsa staining and immunohistochemistry (IHC) using anti-H. pylori antibodies. The sensitivity, specificity, and diagnostic accuracy of Giemsa staining were assessed using IHC as the gold standard. Arbitrary values: Giemsa-positive cases were observed in 65% of samples, while IHC detected H. pylori in 70%. Statistical analysis was conducted using Chi-square tests and kappa agreement. Results: Giemsa staining exhibited a sensitivity of 85%, specificity of 90%, and an overall diagnostic accuracy of 88% when compared to IHC. There was substantial agreement (kappa = 0.76) between the two methods. While Giemsa staining was less expensive and quicker, IHC provided greater specificity, particularly in cases with low bacterial density. Conclusion: Giemsa staining is a reliable, cost-effective method for detecting H. pylori in oral biopsy specimens. However, IHC remains the gold standard due to its higher specificity and ability to detect low-density infections. Combining both techniques may enhance diagnostic accuracy in clinical settings.